Molecular evolution and reassortment dynamics of Orthohantavirus hantanense revealed through longitudinal genomic surveillance in the Republic of Korea - Kyungmin Park; Jongwoo Kim; Seong-Gyu Kim; Won-Keun Kim; Jin-Won Song (Scientific Reports)
Abstract Orthohantavirus hantanense (HTNV), a major cause of hemorrhagic fever with renal syndrome (HFRS), remains a public health concern in East Asia. We investigated its evolutionary history, reassortment, and genetic diversity by analyzing 123 complete genomes from the Republic of Korea (1976–2023), comprising the most comprehensive dataset to date from this endemic region. Bayesian coalescent analyses estimated evolutionary rates ranging from 1.6 to 6.6 × 10⁻⁴ substitutions per site per year, with the Gn protein exhibiting the highest rate, suggesting gene-specific dynamics. Strong purifying selection (nonsynonymous/synonymous ratio < 0.1) was observed across all segments, reflecting substantial evolutionary constraints. Reassortment analysis revealed frequent segment exchanges, particularly involving the L segment, indicating segment compatibility differences and potential effects on viral fitness. Cline analyses identified a hybrid zone approximately 45 km wide in northern regions, highlighting the role of inter-lineage genetic exchange in enhancing viral diversity and adaptability. These findings clarify the evolution and phylogeography of HTNV and underscore the importance of ongoing genomic surveillance for identifying transmission hotspots, detecting emerging variants, and guiding targeted public health strategies to control endemic HFRS outbreaks effectively.